2009
DOI: 10.1186/1477-7827-7-125
|View full text |Cite
|
Sign up to set email alerts
|

Semen molecular and cellular features: these parameters can reliably predict subsequent ART outcome in a goat model

Abstract: Currently, the assessment of sperm function in a raw or processed semen sample is not able to reliably predict sperm ability to withstand freezing and thawing procedures and in vivo fertility and/ or assisted reproductive biotechnologies (ART) outcome. The aim of the present study was to investigate which parameters among a battery of analyses could predict subsequent spermatozoa in vitro fertilization ability and hence blastocyst output in a goat model. Ejaculates were obtained by artificial vagina from 3 adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 58 publications
1
19
0
4
Order By: Relevance
“…While conventional semen analysis can be useful as initial evaluation of a patient's fertility status, there is growing evidence that it has limited value in diagnosing male infertility or predicting success of assisted reproduction (Berlinguer et al, 2009;Björndahl and Haugen, 2008;Ford, 2010;Garrido et al, 2008;Nagler, 2011;Saleh et al, 2003;Shamsi et al, 2010). Although currently not in the battery of routine clinical tests offered to patients, sperm DNA damage has been demonstrated to be a promising tool in determining the male patient's fertility status and to predict successful treatment in terms of the short-term goals of fertilization and pregnancy and the long-term goal of healthy offspring.…”
Section: Discussionmentioning
confidence: 99%
“…While conventional semen analysis can be useful as initial evaluation of a patient's fertility status, there is growing evidence that it has limited value in diagnosing male infertility or predicting success of assisted reproduction (Berlinguer et al, 2009;Björndahl and Haugen, 2008;Ford, 2010;Garrido et al, 2008;Nagler, 2011;Saleh et al, 2003;Shamsi et al, 2010). Although currently not in the battery of routine clinical tests offered to patients, sperm DNA damage has been demonstrated to be a promising tool in determining the male patient's fertility status and to predict successful treatment in terms of the short-term goals of fertilization and pregnancy and the long-term goal of healthy offspring.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies conducted different extenders' (Trisbased, milk powder) positive effects on motility have been notified (1,7,23). In the research conducted it was found that the highest value belonged to 1-c extender and the lowest value belonged to 2-d extender, along with 1-b, 1-d and 2-b extenders values were higher than the control extender.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies conducted on goats, the post-thaw in vitro values of semen frozen with different extenders were evaluated with CASA system (1,7,23). The differences between the data obtained from the study presented and other researches using the same analysis system (SCA) may be caused by the usage of different breeds of goats.…”
Section: Discussionmentioning
confidence: 99%
“…A fertilidade varia substancialmente entre os touros. Em geral, os métodos para estimar a fertilidade são melhores para a identificação de touros com baixa fertilidade do que para classificar touros com boa ou excelente fertilidade (KASTELIC, 2013 (BERLINGUER et al, 2009;VINCENT et al, 2012;LI et al, 2014;OLIVEIRA et al, 2014 …”
Section: Fertilidade Do Tourounclassified
“…Durante as últimas décadas vários trabalhos foram realizados para buscar marcadores moleculares e celulares como ferramenta de avaliação in vitro de amostras de sêmen, mas os resultados são contraditórios (KILLIAN; CHAPMAN; ROGOWSKI, 1993;ZHANG et al, 1999;RITTA, 2004;BERLINGUER et al, 2009;OLIVEIRA et al, 2013a;SELLEM et al, 2015;BATTUT, 2016). Os trabalhos mais recentes incluem a citometria de fluxo, pois esta permite analisar simultaneamente diferentes compartimentos e funções espermáticas em uma amostra mais representativa (HOSSAIN et al, 2011;PEÑA, 2015).…”
Section: Introductionunclassified